Green Production Module Development Through Ecobricks As a Learning Source of Environmental Pollution (Universitas Negeri Semarang, 2020)
This study aims to describe the results of the development of the green production module through ecobricks as a learning source of environmental pollution. Description of the results of the development in the form of validity and practicality. The data obtained from this study are the results of the validation of media experts and green production module experts through ecobricks. The results of the validity of the media experts from the green production module through ecobricks meet the very valid criteria that is 96,6%. The expert content assessment in this module also fulfills the very valid criteria, which is 95,6%. The results of the analysis based on research data indicate that the green production module through ecobricks is feasible to use with an average module validity result of 96,1% with a very valid category. The teacher's response to the practicality of 93,75% with the module criteria is very practical in learning activities. Student responses by 82,8% with very practical criteria used by students in the implementation of learning. Based on this it can be concluded that the green production module through ecobricks is very valid and very practical to be applied in learning environmental pollution material.